Safety and Tolerability of an Ad26.RSV.preF-based Vaccine in a Phase 2b Study in Older Adults. (17th December 2021) - Falsey, Ann; Williams, Kristi; Gymnopoulou, Efi; Bart, Stephan; Ervin, John; De Paepe, Els; Heijnen, Esther; Comeaux, Christy
Abstract: Respiratory syncytial virus (RSV) may cause severe lower respiratory tract disease in older adults and there is currently no approved vaccine. We assessed the safety and reactogenicity of an Ad26.RSV.preF-based vaccine in a randomized, double-blind, placebo-controlled Phase 2b proof-of-concept trial in adults aged ≥65 years (CYPRESS; NCT03982199). Prior to the RSV season, participants were randomized 1:1 to receive an Ad26.RSV.preF-based vaccine or placebo. Solicited adverse events (AEs; fatigue, headache, nausea, myalgia, fever, injection site reactions) and unsolicited AEs were assessed from time of vaccination to Day 8 and Day 29, respectively, in a safety subset of 695 participants (vaccine, n=348; placebo, n=347). All participants were followed for serious AEs (SAEs) until the end of the RSV season or 6 months after vaccination, whichever occurred later. A total of 5728 participants were randomized and received vaccine or placebo (n=2891 in each group). In the safety subset, the frequency of solicited AEs and Grade ≥3 solicited AEs was 51.4% and 3.2% in the vaccine group and 20.2% and 0.6% in the placebo group, respectively. The most frequent solicited AEs in the vaccine group were fatigue, myalgia, headache, and injection site pain/tenderness. The rates of unsolicited AEs and Grade ≥3 unsolicited AEs were similar between the vaccine (16.7% and 1.7%) and placebo (14.4% and 1.4%) groups. In the overall study population, the rate of SAEs was similar between groups (vaccine, 4.6%; placebo, 4.7%); none were considered related to the vaccine. The Ad26.RSV.preF-based vaccine was safe and well tolerated in adults aged ≥65 years.